1982
DOI: 10.1007/bf00548403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of urinary pH on the disposition of methadone in man

Abstract: The influence of urinary pH on the acute disposition of methadone in man was studied in five healthy volunteers. A cross-over experiment was performed in each subject. In the first experiment the subjects were treated with ammonium chloride (urinary pH approximately 5.2) and in the other the urine was made alkaline (pH approximately 7.8) by treatment with sodium hydrogen carbonate. d, l-Methadone-HCl 10 mg (M) was administered intramuscularly on each occasion and blood, saliva and urine levels of M were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1
1

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(30 citation statements)
references
References 14 publications
3
25
1
1
Order By: Relevance
“…Indeed, the importance of pH has been shown previously on the pharmacokinetics of methadone for example [43,44]. Earlier studies have indicated that an increase in methadone excretion has been observed on lowering urinary pH [43]. Indeed, urinary pH was found to affect the renal excretion of methadone (clearance) but also its volume of distribution [43].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, the importance of pH has been shown previously on the pharmacokinetics of methadone for example [43,44]. Earlier studies have indicated that an increase in methadone excretion has been observed on lowering urinary pH [43]. Indeed, urinary pH was found to affect the renal excretion of methadone (clearance) but also its volume of distribution [43].…”
Section: Discussionmentioning
confidence: 92%
“…Earlier studies have indicated that an increase in methadone excretion has been observed on lowering urinary pH [43]. Indeed, urinary pH was found to affect the renal excretion of methadone (clearance) but also its volume of distribution [43]. Urinary pH modulates renal excretion of a number of drugs by the mechanism of nonionic diffusion as described by Milne et al [45].…”
Section: Discussionmentioning
confidence: 97%
“…A study in opiate-tolerant rats [41] has shown that enforced abstinence is associated with an increase in a 1 -acid glycoprotein, a major binding site for methadone in plasma [39]. Furthermore, opiate users about to begin a programme of methadone treatment are reported to have elevated plasma concentrations of this protein (1.22±0.10 s.d.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The picture in urine is often complex; unchanged methadone in urine only represents 2-5% of the total dose, the rest being excreted as metabolites. Furthermore, methadone excretion into urine is pH dependent so that, when urine is acidified for example, the amount of unchanged drug detected in urine is significantly increased [35]. Clinical interpretation is thus affected by inter-and intra-individual variation in values for urinary pH.…”
Section: Measuring the Efficacy Of Methadone Treatmentmentioning
confidence: 99%